Proceedings of International Conference on Computational Intelligence and Data Engineering Proceedings of ICCIDE 2018 - Chaki, Nabendu; Devarakonda, Nagaraju; Sarkar, Anirban; Debnath, Narayan C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book presents high-quality research work on cutting-edge technologies and the most-happening areas of computational intelligence and data engineering. It includes selected papers from the International Conference on Computational Intelligence and Data Engineering (ICCIDE 2018). The conference was conceived as a forum for researchers from academia and industry to present and share ideas and results and allow them to develop a comprehensive understanding of the challenges of technological advancements from different viewpoints. As such, this book helps foster strong links between academia and industry. It covers various topics, including collective intelligence, intelligent transportation systems, fuzzy systems, Bayesian network, ant colony optimization, data privacy and security, data mining, data warehousing, big data analytics, cloud computing, natural language processing, swarm intelligence, and speech processing. .
Performance Evaluation of Guest Operating System Following Obliteration of Pre-Installed Features -- Formalization of SOA Design Patterns Using Model-Based Specication Technique -- Computational Analysis of Differences in Indian and American Poetry -- Feature Selection for Driver Drowsiness Detection -- Monitoring and Recommendations of Public Transport Using GPS Data -- An Efficient Automatic Brain Tumor Classification using LBP Features and SVM based Classifier -- Analyzing Student Performance in Engineering Placement Using Data Mining -- Cepstrum Based Road Surface Recognition Using Long Range Automotive Radar -- Market Data Analysis by Using Support Vector Machine Learning Technique -- Pre-processing Techniques for Detection of Blurred Images -- Automatic Edge Detection and Growth Prediction of Pleural Effusion Using Raster Scan Algorithm -- Automatic Evaluation of Programming Assignments Using Information Retrieval Techniques.
Keywords: Computational intelligence; Data mining; Big data; Computational Intelligence; Data Mining and Knowledge Discovery; Big Data